CUSTOMS ADMINISTRATION OF THE REPUBLIC OF SERBIA IN THE FUNCTION OF ECONOMIC SECURITY - Čudan, Aleksandar L; Kekić, Dalibor D (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
A priority of economic policy is sustainable development with tendency of long-term expansive development and relatively high rate of economic growth. As global economic crisis intensifies causing disturbance in the financial market, at the beginning of the new millennium the economy of the Republic of Serbia entered a turbulent development stage. The link between economy on the one hand, and national security on the other is complex and manifold. It is clear that economic security as a concept and practice has been determined rather diffusely and limited only by the imagination of a person interpreting and studying it within a wide spectrum of activities. The subject of research of this paper is economic security and the role of the Customs Administration of the Republic of Serbia. Through World Customs Organization as well as through cooperation with other customs services and institutions the Customs Administration has been actively involved in both national and international security system, particularly regarding the fight against organized economic crime, which is related to smuggling, money laundering, illegal transfer of foreign currency, corruption, tax evasion, abuse of intellectual property and similar. The results of this research can be used to highlight the significance of economic security within the system of national security. The manner of research includes: selection and application of scientific methods, the selection of data and the scope of research. The significance of research reflects in the fact that the role of the Customs Administration in the function of economic security both as a subject and factor is insufficiently researched in science while at the same time it is a significant element in contemporary social relations. Key words: Customs Administration, economic security, destructions, economic crime